LEGAL NATURE AND PRACTICE OF ANTI-SUIT INJUNCTION ISSUED BY ARBITRAL TRIBUNAL - Bliuvaitė, Marija (Teisė, 2016)
The article analyses legal nature and some practical problems of anti-suit injunctions issued by arbitral tribunals. One part of the article is dedicated to the tendencies of the European Court of Justice regarding the impact of Brussels I Regulation to the anti-suit injunctions granted by arbitral tribunals within the EU. The right of arbitral tribunal to grant anti-suit injunction consists of the right to decide on its own jurisdiction and the right to grant interim measures of protection. Such dual legal nature, on one hand, helps to apply anti-suit injunction flexibly, on the other hand, makes the relations between arbitration courts and national courts chaotic, due to different national legislation. With a view to unify the attitude of the states towards anti-suit injunction, as well as to encourage its effective implementation, it would be advisable, first of all, to unify the definition and establish clear procedural limits for anti-suit injunction, indicating when it has to be applied. Moreover, evaluation of the effect of parallel proceedings on the arbitral case should not be limited to identification of formal links. Also, it is neccessary to clarify criterions, which define abuse of arbitral process in the light of parallel proceedings, and to expand the list of sanctions in order to guarantee enforcement. Brussels I Recast was expected to bring a wider proarbitral perspective of EU and systemically remove all questions related to arbitration from the scope of the Regulation. Such step would confirm the legitimacy of anti-suit injunctions in EU. However, recent decision of European Court of Justice in Gazprom case left some doubts about the tendencies and interpretations of anti-suit injunctions and legal community is still in need of a clearer framework for anti-suit injunctions.